KARAKTERISTIK KIMIA DAN SENSORI PERMEN JELLY KULIT BUAH NAGA (Hylocereus polyrhizus) DENGAN PENAMBAHAN SARI BUAH BELIMBING WULUH (Avverhoa bilimbi L.) - Afifah Izzatu Rahmah; Intan Kusumaningrum; Siti Nurhalimah (Universitas Djuanda, 2024)
ABSTRACT Jelly candy is candy made from filtered fruit juice with gelling additions, has a clear color and soft texture with a certain level of chewiness. Dragon fruit skin contains anthocyanins and is a source of natural antioxidants and contains pectin. Belimbing wuluh contains oxalic acid and citric acid, so it can replace the use of citric acid in making jelly cady. The purpose of this study is the utilization of red dragon fruit peel as pectin and natural coroling in teh manufacture of jelly. This study used a one factor Completely Randomized Design (CRD), namely the concentration ratio of dragon fruit peel extract with star fruit (70:40), (80:30), and (90:20). Product analysis includes sensory test and water content test as a determinant of the selected product. Data analysis used was ANOVA with Duncan’s further test. The selected jelly candy was obtained in the treatment (90:20). The results of the sensory test on jelly candy are bright red to intense red, slightly scented with dragon fruit peel, sweet and slightly sour taste, soft and sticky texture and overall favored by panelists. The selected jelly candy has a moisture content of 34.79%, reducing sugar content of 25.75% and saccharose content of 83.20%. In addition, the selected jelly candy has a high vitamin C content of 1027.14 mg/100g.